Accumulation and regulation of malate in fruit cells - Li-Hua Zhang; Ao-Ning Zhang; Yu Xu; Ling-Cheng Zhu; Bai-Quan Ma; Ming-Jun Li (Fruit Research)
Fruit acidity is an important component of flavor quality in fleshy fruit. The accumulation of malate, the dominant organic acid in the acidity formation of most mature fruit, is highly regulated by metabolism and transportation during fruit development. The knowledge on the mechanism of fruit acidification, as well as the major genes and substances is however still limited. In the present paper, the research advances on the relevance between malate accumulation and the genes associated with malate metabolism and transportation, as well as the transcriptional regulation of malate in fruit was reviewed. Furthermore, positive future research could provide a theoretical reference for optimizing fruit quality and genetic improvement.